Edukasi Pembuatan dan Pemanfaatan Tanaman Sereh Sebagai Minuman Kaya Khasiat - Maulana, Ilham; syari, Delviza; Gulo, Tris Ella Julita; selay, Risma Eka Putri (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The aim of this activity is to provide education on the manufacture and use of lemongrass plants as a drink rich in benefits, which is carried out at Bogor's Sempur Field. Providing simple education about the benefits of lemongrass and lemon drinks, where the content contained in lemongrass is able to reduce hypertension, control blood sugar, and strengthen the nervous system, as well as how to make it, The method used in this activity is to provide education about how to make and the benefits of lemongrass drinks to people who are doing car-free day activities at Bogor's Sempur Field, as well as distributing ready-made lemongrass drinks to residents who are doing car-free day activities in the field. Sempur. The result of this service is that people who come to our service stand receive education about the benefits of lemongrass drinks, how to make them, and ready-made lemongrass drinks.